2016
DOI: 10.3390/en9080613
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Aerodynamic Loads on Offshore Wind Turbines under Typhoon with Full Wind Direction

Abstract: Abstract:Super typhoon activity is likely to make the electric power network fail, or blow the wind-measuring device off, which all lead to the yaw control system of wind turbine being inactive. Under this condition, blades can be blown by the violent side wind from unfavorable directions, and the aerodynamic loads on the wind turbine will be increased by a large amount, which can lead to low-cycle fatigue damage and other catastrophic collapses. So far, not enough consideration has been given to the above pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Chen et al conducted failure investigations of rotor blade damage, tubular tower collapse, and wind turbine (WT) under super typhoons on the southeast coast of Mainland China, and they found that the change of wind direction is critical during typhoons. Lian et al investigated the wind load characteristics of OWTs under typhoon conditions with full 360‐degree wind directions considering the variations in the wind direction and different wind rotor parking positions using a 3‐D numerical simulation. Kim and Manuel carried out a framework for estimation of structural damage to offshore wind plants during hurricanes.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al conducted failure investigations of rotor blade damage, tubular tower collapse, and wind turbine (WT) under super typhoons on the southeast coast of Mainland China, and they found that the change of wind direction is critical during typhoons. Lian et al investigated the wind load characteristics of OWTs under typhoon conditions with full 360‐degree wind directions considering the variations in the wind direction and different wind rotor parking positions using a 3‐D numerical simulation. Kim and Manuel carried out a framework for estimation of structural damage to offshore wind plants during hurricanes.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested conducting an analysis of an idling wind turbine under gust conditions in the typhoon-prone regions. Lian et al [34] numerically simulated the aerodynamic loads on blades with different wind directions based on the CFD method, with consideration of the shutdown of the yaw system during a typhoon. Chen et al [12] calculated the local mean wind profiles at each turbine site using three-dimensional CFD calculation considering the terrain topography of a wind farm reconstructed from global positioning system (GPS) data.…”
Section: Simulation Of Typhoon Aerodynamic Loadmentioning
confidence: 99%
“…The windy South China Sea has also been studied from the other coast line across the Strait, in China. Chinese scholars have analyzed the special weather conditions with focus on the damage inflicted to offshore wind turbines by typhoons which has been coupled with thoughts on potential implications on WTG design efforts [67]. In addition, implications for wind and waves respectively as seen from a floating offshore wind turbine perspective have been analyzed [68,69].…”
Section: Our Asian Case Study Work Outside Chinamentioning
confidence: 99%